Interações Da Criança Surda No Ambiente Escolar: Um Olhar Microssociológico Sobre A Sua Chegada Ao Ciclo I Do Ensino Fundamental - Araujo, Nina Rosa Silva De [UNIFESP] (2017)
This research chose as study object, the interaction of deaf children in the school environment from a micro sociological perspective about the child’s arrival to Elementary School - Cycle I. The study aimed to investigate the presence of deaf children in the school environment, analyzing the interaction, choices and expectations both of deaf children towards the school space and the latter with the deaf child. The field research had ethnographic inspiration providing an approach about the subject from a micro sociological perspective. The theoretical reference of Erving Goffman analyzed the registered scenes, wherewith inventories of gestures and communication strategies were identified among the leading figures of the research. The disability category was not dealt with biological, physiological and anatomic references; however, it was dealt as a category built in the plot of the analyzed figures, whereas it was registered the experience of being deaf before the other and of non-deaf before the deaf.